The neurophysiology of deforming spastic paresis: A revised taxonomy - Baude, Marjolaine; Nielsen, Jens Bo; Gracies, Jean-Michel (Annals of physical and rehabilitation medicine, 2019)
•Deforming spastic paresis around each joint involves 2 interacting diseases, a muscle disease and a neurologic disease.•The muscle disease, called spastic myopathy, is caused by muscle immobilization in short position in the context of paresis, beginning in the hours after paresis onset.•The neurologic disease is aggravated by the muscle disease and comprises 3 disorders of the antagonist: spastic dystonia, spastic cocontraction, and spasticity.•To minimize the deleterious pathophysiological components of deforming spastic paresis, one should start by preserving muscle tissue integrity, as soon as paresis sets in. This paper revisits the taxonomy of the neurophysiological consequences of a persistent impairment of motor command execution in the classic environment of sensorimotor restriction and muscle hypo-mobilization in short position. Around each joint, the syndrome involves 2 disorders, muscular and neurologic. The muscular disorder is promoted by muscle hypo-mobilization in short position in the context of paresis, in the hours and days after paresis onset: this genetically mediated, evolving myopathy, is called spastic myopathy. The clinician may suspect it by feeling extensibility loss in a resting muscle, although long after the actual onset of the disease. The neurologic disorder, promoted by sensorimotor restriction in the context of paresis and by the muscle disorder itself, comprises 4 main components, mostly affecting antagonists to desired movements: the first is spastic dystonia, an unwanted, involuntary muscle activation at rest, in the absence of stretch or voluntary effort; spastic dystonia superimposes on spastic myopathy to cause visible, gradually increasing body deformities; the second is spastic cocontraction, an unwanted, involuntary antagonist muscle activation during voluntary effort directed to the agonist, aggravated by antagonist stretch; it is primarily due to misdirection of the supraspinal descending drive and contributes to reducing movement amplitude; and the third is spasticity, one form of hyperreflexia, defined by an enhancement of the velocity-dependent responses to phasic stretch, detected and measured at rest (another form of hyperreflexia is “nociceptive spasms”, following flexor reflex afferent stimulation, particularly after spinal cord lesions). The 3 main forms of overactivity, spastic dystonia, spastic cocontraction and spasticity, share the same motor neuron hyperexcitability as a contributing factor, all being predominant in the muscles that are more affected by spastic myopathy. The fourth component of the neurologic disorder affects the agonist: it is stretch-sensitive paresis, which is a decreased access of the central command to the agonist, aggravated by antagonist stretch. Improved understanding of the pathophysiology of deforming spastic paresis should help clinicians select meaningful assessments and refined treatments, including the utmost need to preserve muscle tissue integrity as soon as paresis sets in.